(3JPcQI GdcMGdjfs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s ((3GdMSf Hf eMeO GdMfai s)
(3ChdgG (B:s
(3QCi UGMHgG GdTF CcHQ eeG gh GdYdGL (B: (3jLH ChdG Cf JSCd Yf GdJOHjQ GdeJbOe hjchf GdYdGL HMHSg s
(3BNQgG (B:s
(3aEPG JhGRfJ hJYGOdJ bQHJ ef GdGYJOGd GdMbjbi hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3fSNI SGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B50 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs